Transcriptomic profiles of non-embryogenic and embryogenic callus cells in a highly regenerative upland cotton line (Gossypium hirsutum L.) - Li Wen (BMC Developmental Biology, 2020)
Abstract Background Genotype independent transformation and whole plant regeneration through somatic embryogenesis relies heavily on the intrinsic ability of a genotype to regenerate. The critical genetic architecture of non-embryogenic callus (NEC) cells and embryogenic callus (EC) cells in a highly regenerable cotton genotype is unknown. Results In this study, gene expression profiles of a highly regenerable Gossypium hirsutum L. cultivar, Jin668, were analyzed at two critical developmental stages during somatic embryogenesis, non-embryogenic callus (NEC) cells and embryogenic callus (EC) cells. The rate of EC formation in Jin668 is 96%. Differential gene expression analysis revealed a total of 5333 differentially expressed genes (DEG) with 2534 genes upregulated and 2799 genes downregulated in EC. A total of 144 genes were unique to NEC cells and 174 genes were unique to EC. Clustering and enrichment analysis identified genes upregulated in EC that function as transcription factors/DNA binding, phytohormone response, oxidative reduction, and regulators of transcription; while genes categorized in methylation pathways were downregulated. Four key transcription factors were identified based on their sharp upregulation in EC tissue; LEAFY COTYLEDON 1 (LEC1), BABY BOOM (BBM), FUSCA (FUS3) and AGAMOUS-LIKE15 with distinguishable subgenome expression bias. Conclusions This comparative analysis of NEC and EC transcriptomes gives new insights into the genes involved in somatic embryogenesis in cotton.